10 Years' Experience in Balanitis Xerotica Obliterans: A Single-Institution Study - Pradhan, Akhilesh; Patel, Radhika; Said, A. J.; Upadhyaya, Manasvi (European Journal of Pediatric Surgery, 2019)
Introduction Balanitis xerotica obliterans (BXO) is uncommon in children. Diagnosis of the condition is almost always clinical and supported by histology. Our aim was to evaluate the outcomes of children undergoing circumcision for BXO and explore the correlation between surgical and histological findings.Materials and Methods A 10-year retrospective review (2007–2017) of all children, aged 16 and less, undergoing circumcision at a tertiary teaching hospital was conducted. Statistical analysis was performed using Fisher's exact test.Results BXO occurred in 91/1025 (8.9%) children. The highest incidence of BXO was in the 5 to 10 age group (13.3%; p < 0.0001). The commonest symptom was foreskin scarring (62.6%). Intraoperatively, involvement of foreskin alone was seen in 26.4%, foreskin and meatus in 47.2%, and foreskin, meatus, and glans in 26.4%. Preoperatively, 24.2% of patients were prescribed steroid cream. Histologically, all patients showed microscopic changes confirming BXO. A total of 87.9% of patients only had a circumcision, and 11% required a meatal procedure along with the circumcision. Postoperatively, 19.8% of patients required a further procedure after an average duration of 5.8 months (range: 2–12 months); the majority of whom (83.3%) were prescribed postoperative steroid cream.Conclusion Clinical correlation by surgeons has a high degree of accuracy (>90%). Meatal involvement is more common than previously reported. The use of pre- or postoperative steroids does not obviate the need for further surgical procedures. Patients can have recurrent symptoms 1 year following surgery, and prolonged follow-up is necessary.
Keywords: balanitis xerotica obliterans; phimosis; pediatric; circumcision; topical steroids